Isolation, characterization, and pathogenicity of non and myo-inositol utilizing aeromonas species isolated from cultured freshwater fishes in Peninsular Malaysia - Mohd Sayuti, Mohamad Azzam (2022)
Aeromonas spp. are ubiquitous in water bodies ranging from environmental water to aquaculture water. This genus poses a threat to a myriad of hosts, including freshwater fishes. High stocking density and improper farm practices can increase the susceptibility of cultured freshwater fishes to diseases. Motile Aeromonas septicemia (MAS) is a bacterial disease that is caused by Aeromonas spp. and this disease has infected many freshwater fishes, causing huge economic losses to some countries. Furthermore, many studies have reported the presence of multiple virulence genes and antibiotic resistance abilities among these notorious Aeromonas spp. In addition, with the recent reports of the emergence of a hypervirulent pathotype of A. hydrophila (vAh) that can cause persistent MAS, are particularly of increasing concern among researchers and fish farmers. The vAh strain can be distinguished from other non-vAh strain by its ability to utilize myo-inositol as a sole carbon source. However, the contribution of myo-inositol to the virulence of Aeromonas is poorly understood and never recorded in Malaysia. This data on myo-inositol utilizing Aeromonas spp., including vAh, could alarm Malaysia’s freshwater aquaculture on the approaching danger. Therefore, the objectives of this study were to characterize Aeromonas spp. from freshwater fish farms in Malaysia and analyze the isolates for the presence of putative virulence genes and antibiotic resistance abilities, to identify myo-inositol utilizing strain among isolated Aeromonas spp. and elucidate the influence of myo-inositol utilizing ability on their virulence in red hybrid tilapia, and to perform whole-genome sequencing of myo-inositol utilizing Aeromonas spp. Briefly, a total of 124 isolated Aeromonas spp. were collected and screened for putative virulence genes, antibiotic resistance properties, and myo-inositol utilizing ability, from nine fish farms, located in various geographical regions in Peninsular Malaysia. The results revealed that, out of 124 Aeromonas isolates collected, five species of Aeromonas spp., including A. dhakensis, A. hydrophila, A. veronii, A. caviae and A. jandaei, with multiple virulence genes and antibiotic resistance abilities were characterized. Furthermore, only strains of A. dhakensis (2%) and A. hydrophila (20%) were found to have all eight virulence genes studied, and 69% of all Aeromonas spp. have MAR index of more than 0.2. Only one myo-inositol utilizing strain, A. dhakensis 1P11S3 was identified, among 124 Aeromonas spp. Based on its virulence gene assessment, myo-inositol utilizing A. dhakensis 1P11S3 only harbored 5 of the 8 virulence genes tested in this study. In addition, the antibiotic disc susceptibility test revealed that myo-inositol utilizing A. dhakensis 1P11S3 was only resistant to less than 40% of the antibiotics tested. Further analysis was done via an experimental challenge against red hybrid tilapia (Oreochromis sp.) using selected non- and myo-inositol utilizing Aeromonas spp. (n = 6). The LD50-240h result revealed that the lowest were A. dhakensis 4PS2 and A. hydrophila 8TK3 (105 CFU/mL), followed by myo-inositol utilizing A. dhakensis 1P11S3 (107 CFU/mL), A. veronii 6TS5 (107 CFU/mL), A. caviae 7X11 (107 CFU/mL) and the highest was A. jandaei 7KL3 (1011 CFU/mL). Additionally, no significant difference in histopathological changes of the kidney, liver, and spleen, caused by myo-inositol utilizing A. dhakensis 1P11S3, as compared to other non-myoinositol utilizing Aeromonas following experimental challenge in the red hybrid tilapia. Whole-genome sequencing of A. dhakensis 1P11S3 revealed that myoinositol utilizing A. dhakensis 1P11S3 was indeed A. dhakensis, which was the first record of A. dhakensis that utilize myo-inositol as a sole carbon source. Further in silico analysis with other A. hydrophila revealed that they are closely related and inositol catabolism was confirmed to be present in genotypes of A. dhakensis 1P11S3. In conclusion, myo-inositol utilizing ability did not cause significantly increased pathogenicity in A. dhakensis with current disease model. It may be due to different genomic representation of myo-inositol utilizing vAh with A. dhakensis 1P11S3, since both are of different Aeromonas spp. Furthermore, there is a possibility of other virulence factors that are exclusive to only vAh. Nevertheless, horizontal gene transfer may have occurred between the vAh strain and A. dhakensis 1P11S3, which to the author’s knowledge, no study has reported this ability among A. dhakensis. Future studies should be done to knockout the myo-inositol gene cluster from A. dhakensis 1P11S3 and compare its pathogenicity with wild type A. dhakensis, which can further elucidate the influence of myo-inositol gene cluster on the virulence of Aeromonas spp. Nonetheless, findings from this study would provide a recent epidemiological data on Aeromonas spp., that would help in the development of vaccine and therapeutants for a sustainable freshwater aquaculture.